Design of Web-Based Academic Assessement Information System (Case Study in SMAIT TUNAS BANGSA) - Mardiah, Ainal; Sofian, Erza (LPPM of STIMIK ESQ, 2018)
This study aims to provide recommendations designing web-based academic assessment information system in SMAIT Tunas nation to be developed next. This research uses research and development method and uses waterfall model system development. Analysis and systemâs needs design is done with object oriented approach using four UML diagrams namely usecase diagrams, activity diagrams, sequence diagrams, and class diagrams. The design is also equipped with interface design for five actors involved in this system namely admin, homeroom teacher, teachers, parents, and students. The results of this design can be used as a recommendation for SMAIT Tunas Bangsa and IT developer to be implemented.